Multivariate analysis for evaluation of indigenous rice (Oryza sativa L.) accessions collected from Madhya Pradesh - Panika, Naina; Singh, Yogendra; Singh, SK; Sharma, Stuti; Pani, DR (ORYZA-An International Journal of Rice, 2023)
Eighty indigenous rice genotypes were evaluated for twenty-nine quantitative and quality traits, planted in RCBD with three replications. The data on different characters were analyzed through Mahalanobis’ generalized distance D2 (1936) and Principal Component Analysis for estimating genetic diversity and identification of superior rice genotypes. On the basis of genetic distance the 80 genotypes were grouped into 18 clusters following Tocher’s method. Among them, five clusters contain more than one genotype, while thirteen clusters contain single genotype. The genotypes of cluster VIII and IX showed a higher (19816.1) inter cluster distance followed by cluster IV and VIII (12414.7). Cluster V has been discovered to have the largest intra-cluster distance. In order to increase the genetic diversity of rice, genotypes from these clusters may be crossed. On the basis of PCA findings, among all genotypes contributing their presence in more than one PC with high PC score only five genotypes viz., Biranjphool Shivram, Jeera Phool, Basmati Purani, Kardhana Baldev and Kailari Ram Madan confine with favourable yield as well as quality associated PCs, and had excellent remark for both the traits. These genotypes might be utilized in hybridization programme for the transfer of good yield as well as good quality traits in the recipient rice genotypes for the development of promising rice cultivars.